The Qualitative Study of Covid-19 Vaccination in Pregnant Women using Theory of Planned Behavior - Ai Herliani; Novita Novita (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Pregnant women are at risk for COVID-19 or other infectious diseases. Research reports that COVID infection in pregnant women has a mortality prevalence of up to 3%. Given the seriousness of this disease, high and evenly distributed vaccination coverage throughout the region is imperative in order to form herd immunity. The purpose of this study was to determine the reasons for refusal and acceptance of COVID-19 vaccination in pregnant women. This research is a qualitative analytical research using a phenomenological study approach. This research was conducted by Lebak Wangi Health Center, Serang City in May 2023. The total author used 8 respondents consisting of: 2 pregnant women who had been vaccinated, 4 pregnant women who refused to be vaccinated, and 2 triangulators. Data validity will use triangulation and peer debriefing methods. Behavioral belief in pregnant women who receive vaccinations is to have the right information. Meanwhile, respondents who refuse vaccination are believing false information (hoaxes) about vaccines. The subjective norm held by respondents to refuse vaccines is an order from the husband or parents. The reasons cited for control belief include seeing their child sick when vaccinated or seeing family members, neighbors and close associates who report vaccine side effects such as fever, dizziness, and mild flu.